Typification and characterization of the creole pork production system in the Central Region, Mexico - Angel-Hernández, Arturo; García-Munguía, Carlos Alberto; García- Munguía, Alberto Margarito; Valencia-Posadas, Mauricio; Hernández Ruiz, Jesús; Velázquez-Madrazo, Pablo Alfonso (Ecosistemas y Recursos Agropecuarios, 2022)
The objective of the present work was to make a phenotypic characterization and the production system of the Creole pig present in the central region of the Sierra Madre Oriental, in the municipalities of Huehuetla and San Bartolo Tutotepec (Hidalgo) and Atlequizayan, Ciudad de Cuetzalan and Zacapoaxtla (Puebla). Data collection was carried out according to the structured interview technique, where 55 producers willing to participate and who had pigs with cerdo pelon mexicano and cuino characteristics were included. The animals were characterized morphometrically, body weight, heights (withers and rump), lengths (body, trunk and head) were recorded. A factorial analysis by principal components, clusters and hierarchical was carried out. Descriptive statistics and multifactorial analysis of variance were used for non-parametric variables. Two types of backyard production systems were identified for the breeding of Criollo Pigs in the Central Region of the Sierra Madre Oriental, the first is for self-consumption, the second is differentiated by the incorporation of improvements in management, in the form of production, expansive approach. In addition, the native pigs of the region are differentiated in their morphometry depending on their place of origin.